The Effectiveness of Pedagogical Role Online Teachers’ on Students with Difference Learning Style in Their Critical Thinking Using Pbwiki On-Line Learning - Rathakrishnan, Mohan; ., . (International Journal of Engineering and Technology, 2018)
Online learning integrates collaborative learning among students of all level. By using Pbwiki web site, students can create, add, remove and edit content in hypertext quickly and easily. In this paper, a study on the studentsâ€™ different learning style and critical thinking skill conducted to examine the effectiveness of pedagogical roles online teachersâ€™ in General Paper essay writing.Â The studentsâ€™ learning style (active or reflective learning style) is the moderating variable that was investigated to identify whether PBwiki online learning influence their critical thinking in essay writing. A total of 80 Form Six (Grade 12) students from two high schools in Penang were involved in this 2x2 factorial quasi-experimental study. These students have to write and edit their essays in General Studyâ€™s subject with the assistance of pedagogical role online teachers (PROT). Felder and Silverman (1988) instrument was used to measure the moderating variable [1]. Paulâ€™s (1993) model was used to analyze studentâ€™s critical thinking in online General Studies essay writing [2]. The findings show that students who received the PROT treatment performed significantly better in critical thinking score and enhanced studentsâ€™ critical thinking in General Studies essay writing.Â Â